A call for increased integration of experimental approaches in movement ecology - Hansen, K. Whitney; Brand, Jack A.; Aimon, Cassandre; Avgar, Tal; Bertram, Michael G.; Bontekoe, Iris D.; Brodin, Tomas; Hegemann, Arne; Koger, Benjamin; Lourie, Emmaneul; Menezes, Jorge F.S.; Serota, Mitchell; et al. (Biological Reviews, 2025)
Rapid developments in animal-tracking technology have enabled major advances in the field of movement ecology, which seeks to understand the drivers and consequences of movement across scales, taxa, and ecosystems. The field has made ground-breaking discoveries, yet the majority of studies in movement ecology remain reliant on observational approaches. While important, observational studies are limited compared to experimental methods that can reveal causal relationships and underlying mechanisms. As such, we advocate for a renewed focus on experimental approaches in animal movement ecology. We illustrate a way forward in experimental movement ecology across two fundamental levels of biological organisation: individuals and social groups. We then explore the application of experiments in movement ecology to study anthropogenic influences on wildlife movement, and enhance our mechanistic understanding of conservation interventions. In each of these examples, we draw upon previous research that has effectively employed experimental approaches, while highlighting outstanding questions that could be answered by further experimentation. We conclude by highlighting the ways experimental manipulations in both laboratory and natural settings provide a promising way forward to generate mechanistic understandings of the drivers, consequences, and conservation of animal movement.
Keywords: animal movement; anthropogenic influences; causal inference; experimental design; group dynamics; individual variation; social interactions